SKRINING KECACINGAN PADA ANAK SEKOLAH DASAR DAERAH PERDESAAN DI KOTA SALATIGA, PROVINSI JAWA TENGAH INDONESIA - Prima Kurniati Hamzah; Kusnanto Kusnanto; D. Widarsih D. Widarsih (JIK-JURNAL ILMU KESEHATAN, 2017)
In 2012, prevalence of Soil Transmitted Helminths Disease in Salatiga is about 5.12% to 20%. Based on the report of Salatiga Health Department, the prevalence rate did not represent all of secondary schools. Even in 2013, there was a declination in the number of samples dis-screening 26.3%. The purpose of screening is for the reduction prevalence, intensity of intestinal transmintted helminths disease and eradication program in Salatiga. This study was designed by proportional study on 14 th-16th August 2014. Target screening of population was living in poor environmental sanitation, low socio economic and lived in bad health condition. The sample calculation was taken from 64 respondents which consist of students of 1st to 3rd grade. Data colected were collected by direct interview supported clinical reported from doctor. Screening involved two basic procedure; physical examination based on ministry of health and feces examination of stool in the laboratory using eosin technique. Soil transminted helminths prevalence was 3,21% from Ascaris Lumbricoides. Sensitivity, specificity, PPV and NPV based on clinical symptoms include distended stomach helminths (100%,11.29% and 3.51;100%), pale eyes and dirty (100%,27.42% and 4.26%;100%), diarrhea (100%;22.58% and 4%,100%), decreased appetite (100%,33.87% and 4.65%;100%), weight loss (100%;16,13% and 3.7%;100%), lethargy (100%,30.65% and 4.44%;100%), less passion (100%,17.74% and 3.77%;100%), decreased concentration (100%,29.03% and 4.35%;100%), nausea or vomiting (100%,20.97% and 3.92%;100%), a symptoms combination (100%;79,03% and 13.33%;100%). Number of children who did dis-screening sample do not represent the number of elementary school students located in the town of Salatiga. It is very recommended to Salatiga Health Department to conduct screening of the broader target. Then, by providing training in examination of Soil Transmitted Helminths disease in laboratory workers in conducting the examination will produce more accurate result. Moreover, by providing personal hygiene education to elementary school students accompanied by a parent will contribute for good preventive action. Di Kota Salatiga tahun 2012, prevalensi kecacingan cukup tinggi berkisar 5,12-20%. Berdasarkan laporan Dinas Kesehatan Kota Salatiga, seksi penanggulangan penyakit, angka prevalensi tersebut belum mewakili semua sekolah dasar. Tahun 2013 terjadi penurunan jumlah sampel yang diskrinning sebesar 26,3%. Guna menurunkan angka prevalensi penyakit cacingan, memutus rantai penularan, serta meningkatkan derajat kesehatan dan prestasi murid sekolah dasar. Desain studi adalah proportional study yang dilaksanakan pada 14-16 Agustus 2014.  Sasaran skrinning adalah populasi yang tinggal di sanitasi lingkungan buruk, social ekonomi rendah serta tidak berperilaku hidup bersih dan sehat. Berdasarkan perhitungan sampel jumlah minimal yang akan diskrinning adalah 64 orang. Data yang dikumpulkan berdasarkan wawancara dengan murid dan pemeriksaan gejala klinis. Skrinning menggunakan 2 dasar prosedur yaitu gejala klinis berdasarkan kriteria Kemenkes RI dan pemeriksaan feses di laboratorium dengan metode eosin. Prevalensi kecacingan di SD N Blotongan adalah 3,21 % dengan jenis cacing ascaris lumbricoides. Ada pun sensivitas, spesifisitas, PPV dan NPV gejala klinik dari kecacingan yaitu nafsu makan berkurang (100%, 33,33%, 2,33%,100%) mata pucat dan kotor (100%, 26,98%, 2,13%, 100%), berat badan menurun (100%, 16,13%, 3,70% 100%) perut buncit (100%, 11,29%, 3,51%, 100%), Diare ( 0%, 21,88%, 2,13%, 1005), Lesu (0%, 29,69%, 0%, 100%), Tidak bergairah (0%, 17,19%, 0%, 100%), Kosentrasi belajar berkurang (0%, 28,13%,0%,100%), Mual (0%, 20,31%,0%,100%) dan gejala kombinasi (0%, 79,03%, 0%, 100%). Penggunaan alat skrinning kecacingan menggunakan metode aeosin kurang efektif karena tidak dapat menghitung dan mengindetifikasi telur cacing untuk mengetahui intensitas infeksi cacing. Disarankan kepada Dinas Kesehatan agar memperbaiki laboratorium dengan mengganti metode Kato Katz. Selain itu perlunya penyuluhan pada anak sekolah didampingi orang tua di SD Blotongan 1 dan 2 tentang pentingnya hygiene sanitasi terutama personal hygiene dan  melakukan skrining kecacingan dengan sasaran yang lebih luas.